Variation in the correlation between heart rate and session rating of perceived exertion-based estimations of internal training load in youth soccer players - Vahia, D.; Kelly, A.; Knapman, H.; Williams, C. A. (Pediatric Exercise Science, 2019)
Purpose: When exposed to the same external load, players receive different internal loads, resulting in varied adaptations in fitness. In adult soccer, internal training load is measured using heart rate (HR) and session rating of perceived exertion (sRPE) scales, but these have been underutilized in youth soccer. This study investigated the in-season variation in correlation between HR and sRPE estimations of training load for adolescent soccer players. Method: Fifteen male professional adolescent players were monitored for 7 months. Within-participant correlations and Bland-Altman agreement plots for HR and sRPE were calculated for each month to analyze variation over the season and for individual players to analyze the validity of the scale. Results: The monthly correlations ranged from r=.60 to r=.73 (P<.05) and the overall correlation was r=.64 (95% confidence interval, .60-.68; P<.001). Bland-Altman plots showed an agreement of methods. Conclusion: Results showed consistently large correlations for all months. sRPE is a consistent method of measure of internal training load for the entire season for youth soccer players. Validity analysis found no bias in sRPE measurements when compared with HR for all players in the study.